Examining the Relation between Self-reported ASD Symptoms and Sensory Sensitivities from a Community-based Sample of Adults. (18th August 2021) - Barnard-Brak, Lucy; Watkins, Laci; Richman, David M.
ABSTRACT: Atypical responses to sensory stimuli, termed sensory sensitivities, are a commonly reported symptom for individuals diagnosed with Autism Spectrum Disorder (ASD). In this community-based study of 604 adults, the correlation between sensory sensitivities and ASD symptoms was r = 0.23, p < .001, representing a smaller relation than estimates previously reported in the peer-reviewed research. Additionally, when examining only participants who met or exceeded the ASD screening cutoff score, the relation between sensory sensitivities and ASD symptoms was only slightly larger at r = 0.25, p < .001. Forty-four percentage who met the screening cutoff score for ASD also reported the lowest degree of sensory sensitivities. Finally, just over one-third who met the screening cutoff score for ASD had the highest sensory sensitivities. Sensory sensitivities did not appear to be a consistent feature across adults meeting the ASD screening cutoff score, but a proportion meeting the ASD screening cutoff score also exhibited the most extreme sensory sensitivities.